First-trimester screening markers in pregnancies complicated by cervical insufficiency: A comparative retrospective study (Annals of Medical Research, 2025)
Aim: This retrospective study aimed to evaluate the relationship between first-trimester screening markers and cervical insufficiency, comparing biochemical parameters and pregnancy outcomes among women with cervical insufficiency, spontaneous preterm birth, and term pregnancies.Materials and Methods: A total of 248 singleton pregnancies were included and divided into three groups: control (term deliveries, n=121), cervical insufficiency with cerclage (n=60), and spontaneous preterm birth (n=67). First-trimester serum markers including pregnancy-associated plasma protein A (PAPP-A), free beta-human chorionic gonadotropin (β-hCG), nuchal translucency (NT), and alpha-fetoprotein (AFP) were analyzed. Obstetric and neonatal outcomes such as gestational age at delivery, birth weight, Apgar scores, and adverse neonatal outcomes were recorded.Results: No significant differences were observed in first-trimester PAPP-A, β-hCG, NT, and AFP levels between the cervical insufficiency and control groups. However, the spontaneous preterm birth group exhibited significantly lower PAPP-A and higher β-hCG levels compared to both other groups (p < 0.001). Gestational age at delivery, birth weight, Apgar scores, and adverse neonatal outcomes were significantly worse in both cervical insufficiency and spontaneous preterm birth groups compared to controls (p < 0.05).Conclusion: First-trimester biochemical markers have limited predictive value for cervical insufficiency but show significant alterations in spontaneous preterm birth. Cervical insufficiency appears to be a localized structural pathology not reflected by early systemic biochemical changes. Clinical management should prioritize second-trimester cervical length assessment and appropriate interventions over reliance on first-trimester serum markers. Further research is needed to identify specific biomarkers for early detection of cervical insufficiency.